PUCUK REBUNG (SPROUT OF BAMBOO SHOOT) AS A SYMBOL OF RIAU MALAY: AN INQUISITIVE SEMANTIC ANALYSIS (MOTIF PUCUK REBUNG PADA TENUN MELAYU RIAU: ANALISIS SEMANTIK INKUISITIF) - Hermandra Hermandra; Anida Sarudin; Elvi Citraresmana; Silvia Marni; Piki Setri Pernantah; Zulhafizh Zulhafizh (Universitas PGRI Sumatera Barat, 2022)
Inquisitive semantics is defined as a framework in logic and natural language semantics. It deals with a study of meaning that leads to the process of understanding the philosophy and descriptions of Malay ways of thinking. The objective of this study is to find out the meaning of the sprout of bamboo shoot motif (Pucuk Rebung motif) as a symbol of Riau Malay and its correlation to behavior of Riau Malays. This research is a qualitative descriptive study using inquisitive semantic analysis. Inquisitive semantics combines theory, data, and nature in its analysis. The data taken are regarding with one of the motifs used as a Riau Malay symbol, the sprout of bamboo shoot motif. The data were collected by using the observation technique. The data analysis technique was carried out through 3 stages, namely script semantic analysis (to find out the meaning), cognitive semantic analysis (to find out knowledge), and inquisitive semantic analysis (to find out reasons). The research findings revealed that that the sprout of bamboo shoot motif symbolizes high commitment and optimism to achieve goals. The bamboo shoots were chosen because they are known as the batik motif with three parallel stripes and used as border design on the edge of a sarong. The motif makes a person using it confident. The findings also revealed that the Malay people are used to deal with their environment and reflect it as imagery in expressing a piece of advice. The Malay people believe that environment is the best reflection for life.